Suitability of Using the Hamate for Reconstruction of the Finger Middle Phalanx Base: An Assessment of Cartilage Thickness. Issue 3 (August 2019) - Podolsky, Dale J.; Mainprize, James; McMillan, Catherine; Binhammer, Paul
Background: Osteochondral grafts are indicated for reconstructing the finger middle phalanx base when there is greater than 50% involvement of the articular surface and significant comminution. This study aims to compare the cartilage thickness of the distal surface of the hamate to the finger middle phalanx base to assess its suitability as an osteochondral graft. Methods: A 3-dimensional laser scanner and computer modelling techniques were utilized to determine the cartilage thickness of the distal surface of the hamate, and finger middle phalanx base using cadaver specimens. The mean, maximum, and coefficient of variation (CV%; a measure of uniformity of cartilage distribution), as well as cartilage distribution maps were determined. Results: The mean cartilage thickness of the hamate was 0.73 ± 0.08 mm compared to the average mean thickness of the finger middle phalanx base of 0.40 ± 0.12 mm. The maximum cartilage thickness of the hamate was 1.27 ± 0.14 mm compared to the average maximum of the finger middle phalanx base of 0.67 ± 0.14 mm. The CV% of the hamate was 27.8 ± 4.2 compared to the average CV% for the finger middle phalanx base of 26.6 ± 8.1. The hamate and finger middle phalanx base have maximum areas that were most frequently at or spanning the median ridge; however, this was more consistently observed with the hamate. Conclusion: The distal surface of the hamate is a suitable osteochondral graft with respect to cartilage thickness and distribution providing sufficient cartilage for reconstruction of the finger middle phalanx base.